How to do media and cultural studies - Stokes, Jane (SAGE, 2021)
"A favourite with both students and lecturers, How to Do Media and Cultural Studies provides readers with all the knowledge and practical expertise they need to carry out their project or dissertation. Giving them hands-on guidance on managing the whole process, Jane Stokes: Shows students how to identify a topic and create a research question; Guides them through the research process, from getting started through to writing-up; Explores a range of case studies, showing how methods have been applied by others. Expanded and updated throughout, this 3rd edition now includes: Increased coverage of digital media, social media and internet research More practical exercises to help you tie media and cultural theory to your work New guidance on understanding research ethics New guidance on mixing and combining methods How to Do Media and Cultural Studies has inspired thousands of students and researchers to understand why studying media texts, industries and audiences is so important. It is an ideal companion for anyone conducting a research project."--Provided by publisher.